2005
DOI: 10.1016/j.physd.2004.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nearly inviscid Faraday waves in almost circular containers

Abstract: Parametrically driven surface gravity-capillary waves in an elliptically distorted circular cylinder are studied. In the nearly inviscid regime, the waves couple to a streaming flow driven in oscillatory viscous boundary layers. In a cylindrical container, the streaming flow couples to the spatial phase of the waves, but in a distorted cylinder, it couples to their amplitudes as well. This coupling may destabilize pure standing oscillations, and lead to complex time-dependent dynamics at onset. Among the new d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
(74 reference statements)
1
24
0
Order By: Relevance
“…Best et al (2005) for an application to a pacemaker network, or Higuera et al (2005) for an application to Faraday waves.…”
Section: More General Notion Of Slow Manifoldmentioning
confidence: 99%
“…Best et al (2005) for an application to a pacemaker network, or Higuera et al (2005) for an application to Faraday waves.…”
Section: More General Notion Of Slow Manifoldmentioning
confidence: 99%
“…The presence of relaxation oscillations, let alone of canards, is unusual in fluid dynamics, and we believe that our study represents the frrst time that ducks have been found in water. A fortheoming paper describes our results in greater detail [6].…”
Section: Discussionmentioning
confidence: 89%
“…Two types of canards have been identified: phase canards, in which the spatial extent of the localized pattern changes abruptly as an additional wavelength is nucleated or annihilated on either side, and amplitude canards, in which the amplitude temporarily drops to the amplitude of the unstable lower branch of spatially periodic states before abruptly increasing to the amplitude of the stable upper states. Canards are normally considered to be a property of finite-dimensional systems, although there are indications that they should be observable in pattern-forming (i.e., spatially extended) systems and in particular in the Faraday system [16]. It is therefore of particular interest to present clear evidence for such orbits in a partial differential equation.…”
Section: Discussionmentioning
confidence: 99%